Analisa Aerodinamika Body Mobil Listrik Dengan Metode Compputational Fluid Dynamic (CFD) pada Variasi Frontal Area dan Kecepatan Aliran Udara Menggunakan Software Ansys Fluent - Adi Pangestu, Rangga; Asnawi, A; Nayan, Ahmad; Setiawan, Adi; Muhammad, M (Malikussaleh Journal of Mechanical Science and Technology, 2024)
Currently the government is working to achieve a Golden Indonesia 2045 and Indonesia Net Zero Emissions (NZE) 2060. In an effort to reduce carbon emissions, one of the government's efforts is to use electric vehicles in the transportation sector and create an Energy Saving Car (KMHE) competition organized by Ministry of Education, Culture, Research and Technology (Kemendikbudristek). This research was conducted to determine the aerodynamic values and their influence on variations in the frontal area and leading edge of the Pase Team Electric car body at Malikussaleh University. This simulation analysis was carried out using the computational fluid dynamic (CFD) method using Ansys Fluent software as a simulation tool. With variations in air flow speed of 2.7 m/s, 5.5 m/s, 8.3 m/s and 11.1 m/s, the aerodynamic values and influences on each body variation are obtained. For the drag coefficient on a body with a frontal area A=0.48m2, the average value obtained from the three leading edge angles 36áµ’, 15áµ’ and 0áµ’ is 0.151. Then for the lift coefficient, an average value of -0.255 is obtained, which means the body produces a relatively low CD but produces large downforce. For the drag coefficient on a body with a frontal area A=0.39m2, the average value obtained from the three leading edge angles 36áµ’, 15áµ’ and 0áµ’ is 0.134. Then for the lift coefficient, the average value was -0.138. So it can be concluded that by reducing the frontal area on the body and the leading edge angle, the Cd value can be reduced by 11.34% and CL by -46%.